Miri Resident Office / Catherine Urai Laing - Laing, Catherine Urai (2016)
This chapter will discuss and summarize the history and background, vision, mission, function, logo, motto and organizational chart of Miri Resident Office. This chapter also will describe the section within the Miri Resident Office.